Dos detalhes ao manuseio: ensino de configuração eletrônica com o quadro de Bohr - Silva, Leandro Borges Matos da (2023)
FROM DETAILS TO HANDLING: TEACHING ELETRONIC CONFIGURATION WITH THE BOHR MODEL. The trajectory of this research consists of revealing the details of concepts hidden in the structure of sensory material, the Bohr model. With it, we will continue studying the electronic configuration with a quantum mechanical approach. The handling of this tool breaks down the barriers imposed by the abstraction of the content and enhances the cognitive operations and functions resulting from hands- on learning. The study was conducted with forty students from a public school in São Paulo.The students participated in a didactic sequence that involved making predictions, observations and explanations about activities, materials and school content. Their performances were evaluated and categorized on a performance scale as either concrete operational or formal operational. In the context of teaching and learning, we will evaluate the epistemological and pedagogical dimensions, and their impact on the quality of student learning.